Selected Archaeological Materials from Harappan Sites and Their Mesopotamian Correlations. M.A. - Durrani, Farzand Ali (1962)
M. E. L. Mallowan – K. R. Maxwell-Hyslop; Typescript; I. The environmental background of the Indus-Valley and Lower Mesopotamia; II. Stone vases (and ritual slabs) as evidence of connection between M. and the I.-V; III. Lothal Rupar and Rangpur; IV. The architecture of the I.-V. and Mesopotamia; V. Conclusions.